Chronic sinusitis diagnosis and treatment - Korzec, Tomasz; Raczkiewicz, Przemysław; Panek, Eliasz; Jasłowski, Damian; Rzeszutko, Mateusz; Panasiuk, Dominika; Skrętowicz, Mateusz; Szponarowicz, Patrycja; Snopkowski, Bartosz; Sosnowski, Jakub (Journal of Education, Health and Sport, 2023)
The growing popularity and use of endoscopic surgery in the field of otolaryngology prompts an attempt to organize knowledge about possible methods of surgery in the nasal cavity and paranasal sinuses. Chronic sinusitis is an inflammatory process involving the mucous membrane of the paranasal sinuses, lasting more than 12 weeks. The system of fissures in the lateral wall of the nasal cavity is an ostiomal ductal complex, the obstruction of which is the direct cause of chronic inflammation of the paranasal sinuses. FESS is a modern method in which access to the paranasal sinuses is obtained through the nasal cavity. The aim of the procedure is to widen, above all, too narrow sections of the middle meatus and the orifice-ductal complex. Compared to traditional methods, it is less invasive, allows you to regain the proper function of the maxillary sinus and, moreover, allows you to correct a deviated nasal septum, remove or reduce overgrown turbinates during one operation using the same access. Although traditional methods of surgery are still used in some groups of patients, modern minimally invasive endoscopic surgery strongly limits their use and becomes the method of first choice. Method: The literature was reviewed using the Pub med search engine and Google scholar using the words: Chronic nasal sinusitis, reasons of chronic nasal sinusitis, FESS, acute nasal sinusitis, nasal sinusitis radiology.